Clinimetric Properties and Minimal Clinically Important Differences for a Battery of Gait, Balance, and Cognitive Examinations for the Tap Test in Idiopathic Normal Pressure Hydrocephalus. Issue 6 (12th July 2018) - Gallagher, Ryan; Marquez, Jodie; Osmotherly, Peter
Abstract: BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is treated by insertion of a ventricular peritoneal (VP) shunt. To help identify who would benefit from a VP shunt, patients undergo a tap test (TT). Several measures can identify change from a TT, but the magnitude of change and the combination of measures that indicate the improvement from a TT is unclear. OBJECTIVE: To develop minimal clinically important differences (MCIDs) for a battery of gait, balance, and cognitive measures in relation to improvement from the TT, and to identify which combination of measures best identifies when improvement has occurred. METHODS: Observational study of iNPH patients undergoing a TT for consideration of a VP shunt. Patients completed the: The Timed Up and Go (TUG), Timed Up and Go cognition (TUG-C), Performance Oriented Mobility Assessment (Tinetti), and Berg Balance Scale (BBS) pre- and post-TT. A Global Rating of Change scale assessed patients' perceived improvements in gait and balance post-TT. RESULTS: MCIDs for the TT were (calculated as percentage changes): TUG: 13%, TUG-C: 11% Tinetti: 36%, and BBS: 20%. A combination of the TUG-C and Tinetti resulted in sensitivity of 90.28% to identify improvement, while the Tinetti and BBS resulted in specificity of 98.58% to exclude improvement from a TT. CONCLUSION: These MCIDs provide the first evidence to quantify the significance of post-TT symptom changes and provides objective data to guide recommendations for clinical management. Utilizing a combination of measures, and these MCIDs as cut off values, results in high sensitivity and specificity for identifying improvement from a TT.